using Venn diagram prove that for the sets x,yand z.
(x-y) - z = x - (y intersection z)
Answers
Answered by
0
Answer:
follow for more
Step-by-step explanation:
ANSWER
Let Δ=ω
∣
∣
∣
∣
∣
∣
∣
∣
x
x
2
y+z
y
y
2
x+z
z
z
2
x+y
∣
∣
∣
∣
∣
∣
∣
∣
Applying R
3
→R
3
+R
1
, we get
Δ=ω
∣
∣
∣
∣
∣
∣
∣
∣
x
x
2
x+y+z
y
y
2
x+y+z
z
z
2
x+y+z
∣
∣
∣
∣
∣
∣
∣
∣
=(x+y+z)ω
∣
∣
∣
∣
∣
∣
∣
∣
x
x
2
1
y
y
2
1
z
z
2
1
∣
∣
∣
∣
∣
∣
∣
∣
Applying C
1
→C
1
−C
2
and C
2
→C
2
−C
3
, we get
Δ=(x+y+z)ω
∣
∣
∣
∣
∣
∣
∣
∣
x−y
x
2
−y
2
0
y−z
y
2
−z
2
0
z
z
2
1
∣
∣
∣
∣
∣
∣
∣
∣
=(x+y+z)(x−y)(y−z)ω
∣
∣
∣
∣
∣
∣
∣
∣
1
x+y
0
1
y+z
0
z
z
2
1
∣
∣
∣
∣
∣
∣
∣
∣
Expanding along R
3
, we get
=(x+y+z)(x−y)(y−z)(y+z−x−y)
=(x−y)(y−z)(z−x)(x+y+z)
Similar questions
Computer Science,
4 months ago
Math,
4 months ago
Hindi,
4 months ago
English,
8 months ago
Social Sciences,
8 months ago
Social Sciences,
1 year ago